Contaminantes metálicos em contrastes a base de quelatos de gadolínio e reações de transmetalação - Santos, Marlei Veiga dos (2013)
Gadolinium (Gd) is the basis of contrast media most used in magnetic resonance imaging (MRI). Because it is a very toxic metal ion, all Gd-based contrast media present chelating agents in their composition. Gd-based formulations are commercially available in concentrations of 1 and 0.5 mol L-1, which are almost exclusively excreted by the kidneys without producing toxic effects. In 2006, however, two European groups independently suggested a link between the administration of gadolinium chelates and the occurrence of nephrogenic systemic fibrosis (NSF) in patients with renal insufficiency. NSF is a serious disease, which origin is attributed to transmetalation reactions between Gd and endogenous metals. In this work, we used the techniques atomic absorption spectrometry, mass spectrometry with inductively coupled plasma and liquid chromatography with mass detector to investigate metals present as impurities and / or contaminants in five Gd-based contrast formulations and their possible transmetalation reactions. The results showed that several metals are present in the formulations, the rare earth elements (Sc, Y, La, Ce, Pr, Nd, Eu, Tb, Dy, Ho, Er and Tm) and others such as Al, As and Pb, notoriously toxic to humans. To evaluate transmetallation reactions the Gd-DTPA complex (gadopentetate dimeglumine) was used as template model. It was found that practically all elements present as contaminants in the formulation are able to replace Gd in the complex. Even endogenous metals such as Cu and Fe, which do not present any toxicological potential, may cause , due to transmetallation reations, free Gd3 + to be formed.